(untitled) (International Journal of Environmental Sciences, 2025)
Anxiety disorders are the most prevalent group of mental disorders globally, leading to considerable losses in health, functioning and increase of medical costs. Till now, the search for novel pharmacological treatments is driven by the growing medical need to improve on the effectiveness and the side effect profile of existing drugs. In central nervous system, the mitochondrially located translocator protein (18 kDa, TSPO) serves as the rate-limiting step for neurosteroidogenesis and influences GABAergic transmission. Since 5-HT is one of the most comprehensively studied neurotransmitter systems in the anxiety field. The aim of present study is to evaluate the role of seretonergic transmissions in the nicotine induced induced anxiolysis in mice. Our findings demonstrate that nicotine withdrawal markedly exacerbates anxiety and depressive-like behaviors by interfering with brain serotonin metabolism, inflammatory processes, neurotrophic factors, and oxidative balance.